Atlas of Deep Endometriosis MRI and Laparoscopic Correlations (Springer International Publishing, 2018)
This Atlas presents an MRI-based guide to the diagnosis, treatment and follow up of deep endometriosis. Developed by professionals with a extensive clinical experience in the diagnosis and treatment of deep endometriosis, it provides a global overview of the disease, from basic clinical aspects of imaging diagnosis, to the correlation with surgical findings and histopathological results. Deep endometriosis is a serious gynecological condition, which can severely impact on women's quality of life. It shares the main features of regular endometriosis, but also displays a highly infiltrative pattern, involving multiple organs and leading to severe symptoms such as dysmenorrhea, chronic pelvic pain and dyspareunia. Atlas of Deep Endometriosis - MRI and Laparoscopic Correlations is a complete guide, intended for radiologists, gynecologists and all other medical professionals interested on the diagnosis and treatment of deep endometriosis. (NOTE: This title was previously published in 2014 in Portuguese and Spanish and comes from our partnership with Brazilian publisher, Revinter.).